Residents’ perceptions towards illegal household solid waste disposal: A case of Chegutu, Zimbabwe - Tatenda Musasa; Amato Chireshe; Steven Jerie; Thelma Machisi; Tapiwa Shabani; Takunda Shabani (Smart Construction and Sustainable Cities, 2025)
Abstract Solid waste management has been a daunting problem in Zimbabwe over the past few years. The research sought to examine residents’ knowledge, attitudes and perceptions towards illegal household solid waste disposal in ward 8, Chegutu. The study adopted descriptive research design which used qualitative and quantitative data collection methods namely questionnaires, interviews and field observation. A total 55 questionnaires were administered randomly amongst residents who were willing to participate since out of 64 people 9 declined to respond. Interviews were done with purposefully selected key informants which included Environmental Management Agency (EMA) officer, senior health officer from city council and small-scale enterprise owners. Statistical Package for Social Sciences (SPSS) version 21and content analysis was used to analyse quantitative and qualitative data respectively. Results demonstrated existence of 9 major illegal dumpsites in ward 8, Chegutu. Findings revealed types of solid waste namely biodegradable (47.27%), inorganic waste (32.73%), glass and tin (14.55%) and rags, clothes (5.45%). Disposal practices established were open burning (72.73%), resource recovery (14.55), animal feeding (9.09%) and composting (3.64). Results showed that majority of households (50.91%) lacked understanding of waste management. Residents were seen to be oblivious to the state of illegal dumpsites near them as 46% reported that they were not concerned at all and had negative attitudes and perceptions that city council is solely responsible for solid waste management. Research verdicts indicated that solid waste management (SWM) remains a challenge in ward 8, Chegutu as all efforts from city council and EMA have seemingly failed. The study recommends that city council should improve stakeholder participation and use of approaches which support circular economy namely recycle and reuse.